Evaluation of the diffusive gradients in thin films technique using a mixed binding gel for measuring iron, phosphorus and arsenic in the environment. Issue 3 (20th January 2015) - Sun, Qin; Zhang, Liping; Ding, Shiming; Li, Chao; Yang, Jinyan; Chen, Jing; Wang, Peifang
Abstract : Simultaneous measurements of dissolved iron (Fe), phosphorus (P), and arsenic (As) were made using the diffusive gradients in thin films technique equipped with a mixed binding gel impregnated with zirconium oxide and Chelex-100 (ZrO–Chelex DGT). Abstract : Simultaneous measurements of dissolved iron (Fe), phosphorus (P), and arsenic (As) were made using the diffusive gradients in thin films technique equipped with a mixed binding gel impregnated with zirconium oxide and Chelex-100 (ZrO–Chelex DGT). The ZrO–Chelex binding gel exhibited rapid binding dynamics to Fe(ii ), P(PO4 3− ), and As(iii )/As(v ) in mixed solutions of the three elements. The bound Fe, P, and As could be quantitatively recovered using an established four-step elution procedure. Simultaneous measurements of the three elements with ZrO–Chelex DGT were validated through time-series experiments, and there was no influence of pH (4.1 to 7.1) and ionic strength (0.01 to 800 mM). The DGT capacities for As(iii ) and As(v ) were 69.0 μg and 186 μg per device, respectively, which were much greater than those of the widely used ferrihydrite DGT. Applications in synthesized freshwaters and in sediments further confirmed its feasibility in simultaneous measurements in the environment. The present study offered that the ZrO–Chelex DGT will be a useful tool in in situ monitoring of Fe–P–As and assessment of their interactions in the biogeochemical processes.